Alterações moleculares no tumor marrom do hiperparatireoidismo dos maxilares - Letícia Martins Guimarães (2020)
Brown tumors are lesions that result from abnormal bone metabolism in hyperparathyroidism, which is one of the most common endocrine disorders worldwide. Brown tumors can occur in primary, secondary and even in tertiary hyperparathyroidism. It occurs mainly in long bones, but occasionally affects the jaws and, despite its well-known clinical and microscopic features, the molecular pathogenesis of brown tumors remains unclear. Recently, pathogenic mutations in TRPV4, FGFR1 and KRAS were described in giant-cell lesions of the jaws and nonossifying fibromas of the bones (FGFR1 and KRAS), which are histologic mimics of brown tumors. The aim of this study was to investigate in brown tumors of the jaws the presence of mutations in these genes. To assess such mutations, a convenience sample of 13 brown tumors of the jaws associated with primary or secondary hyperparathyroidism was targeted by Sanger sequencing. As mutations in these genes are known to activate the MAPK/ERK signaling pathway, the immunostaining of the phosphorylated form of ERK1/2 (pERK1/2) was also assessed in these lesions. KRAS pathogenic mutations were detected in seven cases (p.G12V n=4, p.G12D n=1, p.G13D n=1, p.A146T n=1). KRAS variants of unknown significance, p.A134T and p.E37K, were also detected. All samples showed wild-type sequences for FGFR1 and TRPV4 genes. The activation of the MAPK/ERK signaling pathway was demonstrated by pERK1/2 immunohistochemical positivity of the brown tumors´ mononuclear cells. In conclusion, mutations in KRAS and activation of the MAPK/ERK signaling pathway were detected in brown tumors of hyperparathyroidism of the jaws, expanding the spectrum of giant cell lesions whose molecular pathogenesis involve RAS signaling